Kebijakan Pemerintah Daerah: Pendidikan, Pelatihan, dan Peningkatan Infrastruktur Kerja Meningkatkan Kinerja Pemadam Kebakaran - Limariana; Hidayat, Bachtari Alam; Maulana (Jurnal Bina Praja, 2024)
The performance of firefighters is a crucial factor in ensuring public safety and the effectiveness of fire response, making capacity building and infrastructure support a priority. This research aims to comprehensively explore and analyze the impact of education, training, and work infrastructure on the performance of firefighters in OKI Regency. The method used in this study is a quantitative approach, applied to the Fire Department of the Civil Service Police Unit and Fire Department of OKI Regency in June 2024. The research population consists of 187 firefighters and staff members of the Fire Department in OKI Regency. A sample of 99 respondents was selected using random sampling from the entire population. The results of this study indicate that education, training, and infrastructure have a positive and significant effect on the performance of firefighters in OKI Regency. Education is the dominant variable influencing the performance of firefighters in OKI Regency. Human resource development policies in the fire department can focus on improving competencies through formal and non-formal education, as well as enhancing the quality of work facilities to support operational duties.